The Use of low density Polyethylene carry-bags waste in Hot Asphalt paving mixtures (University of Khartoum Engineering Journal, 2022)
This paper reports an investigation on the effect of shreded low density polyethylene (LDPE) as abitumen modifier on the permanent deformation of asphalt concrete using Marshall Design parameters. Theparameters assessed include the compacted hot-mix density, the percentage of air voids in the mixture, and in themineral aggregate, the percentage of voids filled with bitumen, in addition to Marshall Stability and flow. Theeffect of LDPE on some physical properties such as penetration, softening point and ductility was alsoinvestigated. Bitumen was mixed with the LDPE 2 - 10% by weight of bitumen at 160-180°C and it was foundthat Marshall Samples prepared with the modified binder provide the specification limits and that using higherpercentage of plastics waste causes the polymer to separate from the blend. A modified technique was developedwhere the stone aggregate was coated with molten LDPE(10-25%) , the plastics waste coated aggregate (PCA)was then used as the raw material for flexible construction. PCA shows better binding properties. It has lesswetting property with much less voids and higher Marshall Stability value.